Role of Blockchain Technology in Enhancing Data Security in Germany - Meyer, Felix (Journal of Technology and Systems, 2024)
Purpose: To aim of the study was to analyze the role of blockchain technology in enhancing data security. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Blockchain technology is increasingly recognized in Germany for its potential to enhance data security across various sectors. Its decentralized and immutable nature significantly reduces the risks of data tampering and unauthorized access, thereby fostering trust among users. In industries such as finance, healthcare, and supply chain management, blockchain provides transparent and secure methods for recording transactions and managing sensitive information. Additionally, German regulatory frameworks are evolving to accommodate blockchain applications, promoting innovation while ensuring compliance with data protection laws like the GDPR. Unique Contribution to Theory, Practice and Policy: Technological acceptance model (TAM), diffusion of innovations (DOI) & resource-based View (RBV) may be used to anchor future studies on the role of blockchain technology in enhancing data security. Organizations should implement pilot projects to assess the effectiveness of blockchain in enhancing data security in their specific contexts. Policymakers should develop clear regulatory frameworks to support the adoption of blockchain technology across sectors.